Physico-chemical and functional properties of unripe plantain and Bambara groundnut flour blends for doughnut production - Bennett Dzandu; Evans Tettey; Michael Bruce-Adjei (Cogent Food & Agriculture)
This study evaluated the quality characteristics of doughnuts made from blend of plantain (PF) and Bambara groundnut (BGF). Four blends specifically PF90%:BGF10%, PF85%:BGF15%, PF80%:BGF20% and PF75%:BGF25% were formulated. Their composition and functional properties as well as attributes of the doughnuts were evaluated. Also, the sensory acceptability of the doughnuts was evaluated. Moisture and fat content the of blends was less than 6% and 4%, respectively, ash content was up to 2.31% and carbohydrates ranged from 69.50 to 92.12%. BGF recorded the highest protein value of 20.35%. The highest bulk density reported was 0.98 g/ml. Water absorption capacity ranged from 50.81 to 66.43% at 27°C and 51.20 to 76.53% at 70°C. The average oil absorption capacity was 49.24%. Emulsion capacity and stability were affected by the amount of BGF. Microbial analysis showed that the doughnuts were safe to eat. The overall sensory scores for the doughnuts ranged from 5.79 to 7.10. Likewise, the doughnuts were acceptable to consumers with an average rating of 7 out of 9. The results of this study show that the Bambara groundnut-plantain blend is suitable for baked goods such as doughnuts and can also be used as an ingredient in various food formulations, especially gluten-free products.